Real Business Cycle Views of the Great Depression and Recent Events: A Review of Timothy J. Kehoe and Edward C. Prescott's Great Depressions of the Twentieth Century - Temin, Peter (Journal of Economic Literature, 2008)
This book collects essays, most of which were published earlier, into an advertisement for real business cycle (RBC) analysis. Half of the essays discuss the Great Depression; half discuss events of the 1980s and 1990s. They all use the general equilibrium model of economic growth to analyze short-run fluctuations in the rate of economic growth of various countries. I find that the use of closed economy models without frictions is not useful for the analysis of short-run variations in the rate of economic growth. Almost all of these essays end by claiming that variations in the rate of GDP growth were due to changes in the rate of total factor productivity (TFP) growth. They do not provide any explanation for fluctuations in the rate of TFP growth, leaving the reader no closer to understanding these periods of depression and slow growth. I discuss in turn the essays on the Great Depression, the essays on more recent fluctuations, and the definition of “great depressions” used in this volume.